2019
DOI: 10.1016/j.econmod.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and household expenditure behaviour: Evidence from Senegal∗

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 34 publications
4
32
0
2
Order By: Relevance
“…The third perception is that remittances are fungible and that they are treated the same way as income from traditional sources. This perception is supported by the following studies; Randazzo and Piracha (), Castaldo and Reilly (), and Zarate‐Hoyos (). The discussion of perception of remittances so far explains the linkage between remittances and recipient's income and wellbeing but has nothing to say about recipient's income standing relative to others in the society.…”
Section: Why Remittances Might Impact On Poverty and Inequalitysupporting
confidence: 59%
“…The third perception is that remittances are fungible and that they are treated the same way as income from traditional sources. This perception is supported by the following studies; Randazzo and Piracha (), Castaldo and Reilly (), and Zarate‐Hoyos (). The discussion of perception of remittances so far explains the linkage between remittances and recipient's income and wellbeing but has nothing to say about recipient's income standing relative to others in the society.…”
Section: Why Remittances Might Impact On Poverty and Inequalitysupporting
confidence: 59%
“…For example, several studies confirmed that these income flows support resource‐constrained households for the enrolment and maintenance of children in school and for improving the quality of their educational investment (Cox Edwards & Ureta, ; Salas, ). These potential benefits may be counterbalanced by the direct costs of migration and the indirect costs in terms of reduced incentives to labor supply and rural productivity of members left behind, and skilled workers being lost (brain drain) (Acosta, Fajnzylber, & Lopez, ; Adams & Cuecuecha, ; De Haas & Rodríguez, ; Lokshin, Bontch‐Osmolovski, & Glinskaya, ; Randazzo & Piracha, ; Taylor & Lopez‐Feldman, ) . Moreover, evidence has been reported of some negative effects of migration on human capital investment as a result of parental absence (Grigorian & Melkonyan, ; Hanson & Woodruff, ; Hildebrandt & McKenzie, ; McKenzie & Rapoport, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most of the remittances are spent for unproductive equity. Migrant workers prefer to spend the remittance for housing and land, debt repayment and saving as the altruism and ethnic ties play pivotal role in diaspora investment [15]. Unless social capital is quite solid, the diaspora investment seems to be another utopia policy, which may rely on social capital [16].…”
Section: B Assumptionmentioning
confidence: 99%